OPTIMIZATION OF OIL PALM PLANTATIONS IN SDGS-BASED COMMUNITY EMPOWERMENT - Karina, Rahmah; Arianti, Dwi; Lestari, Sri Utami; Siadari, Ulidesi; Yanita, Mirawati (Journal of Agri Socio Economics and Business, 2025)
This research aims to optimize the management of oil palm plantations in the context of community empowerment that contributes to the achievement of Sustainable Development Goals (SDGs). The scope of the research includes analyzing the social, economic, and environmental impacts of oil palm plantations on the welfare of communities around the plantations. We obtained the secondary data for this study from various reliable sources and used SPSS and EViews software for analysis. There was a study that used regression analysis to find the connection between economic indicators, like income and job opportunities, and environmental and social variables important to the SDGs. The results show that sustainable management of oil palm plantations can improve the welfare of local communities, particularly through increased income and reduced economic disparities. In addition, this study also reveals the importance of implementing environmentally friendly practices in maintaining the sustainability of plantations. The conclusion of this study is that optimizing the management of oil palm plantations can be an effective tool in community empowerment and achieving SDG targets, provided that there is a balance between economic, social, and environmental aspects. Implementation of policies that support sustainable plantation practices and community empowerment is necessary to achieve maximum results